2017
DOI: 10.1038/s41598-017-05147-w
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lipid content reorganizes gut microbiota and probiotic L. rhamnosus attenuates obesity and enhances catabolic hormonal milieu in zebrafish

Abstract: In the present study, we explored whether dietary lipid content influences the gut microbiome in adult zebrafish. Diets containing three different lipid levels (high [HFD], medium [MFD], and low [LFD]) were administered with or without the supplementation of Lactobacillus rhamnosus (P) to zebrafish in order to explore how the dietary lipid content may influence the gut microbiome. Dietary lipid content shifted the gut microbiome structure. The addition of L. rhamnosus in the diets, induced transcriptional redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 57 publications
3
53
0
2
Order By: Relevance
“…It is advantageous due to its extremely high throughput and does not require much specialised equipment. More recently, the protozoan Paramecium caudatum, a natural prey for larval zebrafish, has been adapted as a vehicle for foodborne infection models (Fan et al, 2019;Flores et al, 2019;Stones et al, 2017). Immersion cannot be applied to strictly anaerobic microbes.…”
Section: Adaptive Immunity and The Gi Tractmentioning
confidence: 99%
See 3 more Smart Citations
“…It is advantageous due to its extremely high throughput and does not require much specialised equipment. More recently, the protozoan Paramecium caudatum, a natural prey for larval zebrafish, has been adapted as a vehicle for foodborne infection models (Fan et al, 2019;Flores et al, 2019;Stones et al, 2017). Immersion cannot be applied to strictly anaerobic microbes.…”
Section: Adaptive Immunity and The Gi Tractmentioning
confidence: 99%
“…For some GI pathogens, in particular those for which zebrafish are not a natural host, immersion does not lead to robust intestinal colonisation (e.g., Tysnes, Jørgensen, Poppe, Midtlyng, & Robertson, 2012;Stones et al, 2017 etc.). More recently, the protozoan Paramecium caudatum, a natural prey for larval zebrafish, has been adapted as a vehicle for foodborne infection models (Fan et al, 2019;Flores et al, 2019;Stones et al, 2017). The protozoan internalises bacteria into storage vacuoles, and following uptake of Paramecia by the zebrafish and degradation of the protozoan in the foregut, the bacterial load is released into the middle intestine.…”
Section: Adaptive Immunity and The Gi Tractmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies focused their attention on the use of bacteria as probiotics and their capability to modify host nutrient metabolism and energy balance (Falcinelli et al., , , ; Hemarajata & Versalovic, ; Maradonna et al., ); however, last evidences have shown that many eukaryotic species, such as yeasts and yeast nucleotides, positively regulate host metabolism (Ringø, Erik Olsen, Gonzalez Vecino, Wadsworth, & Song, ).…”
Section: Discussionmentioning
confidence: 99%